Language Errors in Different Foreign Language Teaching Perspectives - Pawłowska, Agnieszka (Glottodidactica, 2010)
The article focuses on the problem of language errors that – more often than not – still tends to be regarded as a marginal phenomenon which does not deserve any particular attention. An attempt is made at analyzing the concept of a language error and tracking the approach to it adopted in selected language teaching methods, arriving finally at the language error theory in modern language teaching.